Enhanced binding of calmodulin to the ryanodine receptor corrects contractile dysfunction in failing hearts - Hino, Akihiro (Oxford University Press, 2012)
AIMS: The channel function of the cardiac ryanodine receptor (RyR2) is modulated by calmodulin (CaM). However, the involvement of CaM in aberrant Ca(2+) release in diseased hearts remains unclear. Here, we investigated the pathogenic role of defective CaM binding to the RyR2 in the channel dysfunction associated with heart failure. METHODS AND RESULTS: The involvement of CaM in aberrant Ca(2+) release was assessed in normal and pacing-induced failing canine hearts. The apparent affinity of CaM for RyR2 was considerably lower in failing sarcoplasmic reticulum (SR) compared with normal SR. Thus, the amount of CaM bound to RyR2 was markedly decreased in failing myocytes. Expression of the CaM isoform Gly-Ser-His-CaM (GSH-CaM), which has much higher binding affinity than wild-type CaM for RyR1, restored normal CaM binding to RyR2 in both SR and myocytes of failing hearts. The Ca(2+) spark frequency (SpF) was markedly higher and the SR Ca(2+) content was lower in failing myocytes compared with normal myocytes. The incorporation of GSH-CaM into the failing myocytes corrected the aberrant SpF and SR Ca(2+) content to normal levels. CONCLUSION: Reduced CaM binding to RyR2 seems to play a critical role in the pathogenesis of aberrant Ca(2+) release in failing hearts. Correction of the reduced CaM binding to RyR2 stabilizes the RyR2 channel function and thereby restores normal Ca(2+) handling and contractile function to failing hearts.